2017
DOI: 10.1177/0969733017707008
|View full text |Cite
|
Sign up to set email alerts
|

Beyond demarcation: Care ethics as an interdisciplinary field of inquiry

Abstract: We propose to conceive care ethics as an interdisciplinary field of inquiry, incorporating a dialectical relation between empirical research and theoretical reflection. Departing from the notion of caring as a practice of contributing to a life-sustaining web, we argue that care ethics can only profit from a loosely organized academic profile that allows for flexibility and critical attitude that brings us close to the good emerging in specific practices. This asks for ways of searching for a common focus and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 16 publications
0
54
0
Order By: Relevance
“…Yet new ways of looking can highlight what is taken for granted, its shortcomings and possible alternatives. We suggest that next steps include research into maternity services using a care ethical approach, to identify and describe current power relationships and their effects as they exist in maternity care, and what constitutes 'morally good' 27 practice from the care ethics perspective.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet new ways of looking can highlight what is taken for granted, its shortcomings and possible alternatives. We suggest that next steps include research into maternity services using a care ethical approach, to identify and describe current power relationships and their effects as they exist in maternity care, and what constitutes 'morally good' 27 practice from the care ethics perspective.…”
Section: Resultsmentioning
confidence: 99%
“…Ethics of care has developed over the last 40 years from diverse areas of study: feminism, education, psychology, political science, nursing and philosophy, drawn together by an interest in care as practice, and guiding concepts that include relationality, contextuality, vulnerability, embodiment and attention to power. 27 Carol Gilligan in a critique of Kohlberg's theory of moral development, 28 which identified that boys were able to reach a higher level of moral development than girls, argued that rather than exhibiting a less developed moral outlook, the girls in the study instead solved ethical dilemmas with an eye to responsibility, relationships and individual circumstance (in other words, they used an 'ethic of care'), rather than relying on abstract rules or principles (which Gilligan came to call an 'ethic of justice').…”
Section: Ethics Of Carementioning
confidence: 99%
“…However, scholars do not unanimously agree on a definition for interdisciplinary compassion (Klaver et al, 2014;Leget et al, 2017). Still, meaningful understanding of compassion and collaboration exists.…”
Section: Outer Circle Of Framework: Transformation Compassion and Hmentioning
confidence: 99%
“…As a result, what fields such as nursing ethics has done was use it to inquire about ethical issues in care. In utilizing it, this led to recent literature concluding that ethics of care is an interdisciplinary field of inquiry which is driven by social concerns (Leget, Nistelrooji & Visse, 2019). Additionally, what was discovered was issues surround medical practice, values and morality.…”
Section: Ethics Of Care and Nursing Ethicsmentioning
confidence: 99%